Functions of the APP gene family in the nervous system: insights from mouse models - Aydin, Dorothee; Weyer, Sascha W.; Müller, Ulrike C. (Experimental brain research, 2012)
The amyloid precursor protein (APP) plays a key role in the pathogenesis of Alzheimer's disease (AD), as proteolytical cleavage of APP gives rise to the β-amyloid peptide which is deposited in the brains of Alzheimer patients. During the past years, intense research efforts have been directed at elucidating the physiological function(s) of APP and the question of whether a perturbation of these functions contributes to AD pathogenesis. Indeed, a growing body of evidence has accumulated supporting a role of APP and the two closely related homologues APLP1 and APLP2 in various aspects of nervous system development and function, in particular, for synapse formation and function. This review summarizes recent insights into the in vivo role of the APP gene family from mice lacking individual or combinations of APP family members, with particular emphasis on recently generated knockin mice to examine the in vivo relevance of distinct functional domains.